2004
DOI: 10.1021/ja0389974
|View full text |Cite
|
Sign up to set email alerts
|

Stannaacetylene (RSn⋮CR‘) Showing Carbene-like Reaction Mode

Abstract: Photolysis of diazomethylstannylene 2 (ArSn-C(N2)Si(i-Pr)3, Ar = C6H3-2,6-Tip2 (Tip = C6H2-2,4,6-(i-Pr)3)) generated formal stannaacetylene 1 as a reactive intermediate, which was evidenced by the formation of cyclic arylalkylstannylene 4 via an intramolecular carbene insertion to a CH bond of isopropyl groups. The structures of the compounds 2 and 4 were fully characterized by X-ray crystallography. Stannaacetylene 1 was directly observed by laser flash photolysis of 2; lambdamax = 355 nm, tau = 50 ms at room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
34
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 22 publications
(8 reference statements)
6
34
0
4
Order By: Relevance
“…ular for germanium and tin: for these elements stable dicoordinated compounds REX (with X groups susceptible to substitution, for example in salt metathesis reactions) have been known for several years. Consequently, in 2001 the Couret group [8] and three years later Sakamoto, Kira, and coworkers [9] provided evidence for short-lived germynes and stannynes that form during photolysis of the corresponding methyldiazo compounds (Scheme 2). In both cases only trapping products, either from intermolecular (E = Ge) or intramolecular follow-up reactions (E = Sn) were isolated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ular for germanium and tin: for these elements stable dicoordinated compounds REX (with X groups susceptible to substitution, for example in salt metathesis reactions) have been known for several years. Consequently, in 2001 the Couret group [8] and three years later Sakamoto, Kira, and coworkers [9] provided evidence for short-lived germynes and stannynes that form during photolysis of the corresponding methyldiazo compounds (Scheme 2). In both cases only trapping products, either from intermolecular (E = Ge) or intramolecular follow-up reactions (E = Sn) were isolated.…”
mentioning
confidence: 99%
“…Photolysis experiments at 77 K in a methylpentane matrix indicated that the stannyne persists under these conditions and laser flash photolysis experiments suggested a lifetime of approximately 50 ms at room temperature. [9] In the case of silicon the synthesis of the intramolecular phosphanyl-stabilized chlorosilylene 7 paved the way for the preparation of silyne 6 (Scheme 3). [5] Further functionalization of silylene 7 to give diazomethylsilylene 8 and its photolysis at À60 8C gave the dark red silyne 6 in 68 % yield.…”
mentioning
confidence: 99%
“…By photolyzing REC(N 2 )R′ to denitrogenation following by capture reactions of the formed intermediate, Bibal et al. [7] and Setaka et al [8] have indirectly shown the existence of the triply bonded RE≡≡CR′(E=Ge, Sn). However, for Pb≡≡C triply bonding, to the best of our knowledge, we are not aware of any theoretical and experimental reports.…”
Section: Introductionmentioning
confidence: 99%
“…B. bei Salzmetathesen sind) zugänglich. Konsequenterweise konnten 2001 die Gruppe um Couret [8] und drei Jahre später Sakamoto, Kira et al [9] Hinweise auf kurzlebige Germine und Stannine während Photolysereaktionen der entsprechenden Methyldiazoverbindungen vorlegen (Schema 2). In beiden Fällen wurden nur Abfangprodukte durch intermolekulare (E = Ge) oder intramolekulare Folgereaktionen (E = Sn) isoliert.…”
unclassified
“…50 ms bei Raumtemperatur schließen. [9] Im Falle des Siliciums bereitete die Synthese des intramolekular phosphanylstabilisierten Chlorsilylens 7 den Weg für die Synthese des Silins 6 (Schema 3). [5] Eine weitere Funktionalisierung des Silylens 7 zum Diazomethylsilylen 8 und dessen anschließende Photolyse bei À60 8C ergaben das dunkelrote Silin 6 in 68 % Ausbeute.…”
unclassified